The Cantonal Structure Plan in Zurich - Planning Instruments for Shaping Regions. - Natrup, Wilhelm (Lit, 2020)
The Canton of Zurich is located in the middle of a metropolitan area with impressive economic potential. The high quality of life there is an outstanding location factor and is strongly influenced by the wide variety of nearby environments. There are plans to consolidate these advantages in the future. Considerable challenges are posed, however, by sustained population growth, demographic development and social change, the rising demand for convenience, the need to upgrade built-up areas and the guaranteeing of high quality with regard to built-up areas and building culture. Finally, an intact landscape is becoming the key location factor. Particularly attractive are not only larger connected landscape areas with a high value in terms of nature and the experience they offer, but also traditional agricultural landscapes. Landscape and open space in built-up areas and their environs are also gaining in significance. The aim of spatial development in the Canton of Zurich is to conserve the diversity of living and landscape spaces, to promote the qualities they offer even more effectively and to make them better from the perspective of the experience they provide.
Keywords: Stadtregion; Metropolregion; Kantonalplanung; Regionalplanung; Regionalstruktur; Polyzentralität; Landschaftsraum; Landschaftsschutz; Weicher Standortfaktor; Zersiedelung; Flächensteuerung